Mental Health of Human trafficking; A Systematic Review - Awaliyah Muslimah Suwetty; Asti Melani Astari; Titin Andri Wihastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2019)
Human trafficking is being global crime worldwide. The practice of human trafficking in the form of human exploitation implicated in human rights violations. Survivors of human trafficking will experience health problems both physical and mental problems. The purpose of this systematic review was to identify and summarize the mental health problems of human trafficking victims. Systematic search conducted on March 12, 2019 in data of Proquest, Springer Link, and Scopus by keyword *human health of human trafficking* between the years of 2013-2018. The result of this search found 14 journals that match with inclusion criteria. The inclusion criteria were peer-reviewed journal articles, written in English, all forms of exploitation, the samples are aged >15 years old. The results shown the incidence of human trafficking greatly affected the mental health of victim. Victims experienced anxiety, depression, isolation, disorientation, aggression, suicidal ideation, attention deficit, psychotic disorders, behavioral and post-traumatic stress disorder (PTSD). For further research required in efforts to overcome the mental health impact of human trafficking victims. The focus on preventing efforts was through government campaigns, IOM and law enforcement and also the fulfillment of the rights of human trafficking victims